2018
DOI: 10.1589/jpts.30.169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12-week circuit exercise program on obesity index, appetite regulating hormones, and insulin resistance in middle-aged obese females

Abstract: [Purpose] The purpose of this study is to investigate the effects of circuit exercise on obesity index, appetite regulating hormones and insulin resistance in middle-aged obese women. [Subjects and Methods] The subjects of this study were 26 obese middle-aged women who were selected among participants in exercise class at K Region Health Promotion Center in South Korea and were randomly assigned to the exercise group (n=13; age 50.15 ± 3.82, % body fat 38.79 ± 3.28) and the control group (n=13; age 49.84 ± 2.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 48 publications
1
14
1
Order By: Relevance
“…Thus energy expenditure changes may affect the amount of leptin via the exercise (31). The findings of the present research were inconsistent with the findings of other researchers with respect to the effect of resistance exercise on leptin in which it was demonstrated leptin change was associated with a decrease in weight (32). Resistance training may lead to a lower energy consumption state as the time of exercise continues; this kind of exercise compared with aerobic and concurrent exercise results in maintaining body mass fatfree through a lower metabolic rate.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus energy expenditure changes may affect the amount of leptin via the exercise (31). The findings of the present research were inconsistent with the findings of other researchers with respect to the effect of resistance exercise on leptin in which it was demonstrated leptin change was associated with a decrease in weight (32). Resistance training may lead to a lower energy consumption state as the time of exercise continues; this kind of exercise compared with aerobic and concurrent exercise results in maintaining body mass fatfree through a lower metabolic rate.…”
Section: Discussioncontrasting
confidence: 99%
“…The literature search identified 840 records. After screening of titles, abstracts, and full texts, 80 relevant studies [ 46 125 ] were identified and included in the final analysis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of 21 chronic exercise studies that measured TG/ghrelin, two-thirds of studies showed an increase in circulating levels. The latter studies included children [ 104 , 114 ], youth/young adults [ 112 , 118 , 122 ], adults [ 115 , 116 , 121 , 125 ], or seniors [ 103 , 113 , 120 , 123 ], who were either active normal weight [ 112 , 120 , 122 ] or inactive overweight/obese [ 103 , 104 , 113 116 , 118 , 121 , 123 , 125 ] individuals. The training was based on moderate- or high-intensity aerobic [ 112 116 , 123 ], resistance [ 122 ], combined [ 103 , 104 , 120 , 121 , 125 ] or intermittent [ 118 ] exercise.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 Studies have suggested an important role of physical exercise in the regulation of. [17][18][19][20] Among the different modalities, high intensity interval training (HIIT) has been used as a strategy to prevent metabolic syndrome. 21 HIIT can be characterized by short duration sessions composed of high intensity repetitions, interspersed with active or passive rest 22 .There is evidence that HIIT is able to induce lipolytic hormone secretion, probably by the action of IGF-1 on protein kinase B stimulation and by the signaling of testosterone in the androgen receptor, in addition to increasing oxidative capacity, being directly related to the reduction of metabolic disturbances.…”
Section: Introductionmentioning
confidence: 99%